Modelagem lógica de senescência celular humana - Ferreira, Cecilia Perobelli (2012)
After the progressive telomere shortening in successive cell divisions, normal somatic cells undergo a growth arrest called cellular senescence that occurs due to incomplete DNA replication. Senescence can also be activated by various types of stressful stimuli, including aberrant oncogenic signaling, oxidative stress and DNA damage. Senescent cells have limited proliferative capacity and seems to play an important role in tumorigenesis. They are also involved in the inflammation associated with aging and cancer progression. The process of senescence vary significantly between cells, but the different paths for the aging, however, converge to p53 and pRB. The network simulation is based on the model proposed by Porath using a Boolean model to represent the state of activation of genes involved, including the p16-pRb and p53-p21 pathways. The simulation includes 23 nodes representing the genes of the regulatory network where one of them represents the activation of the senescent state as a result of network processing. Experiments with human fibroblasts indicate that inactivation of both genes, p53 and pRB is necessary to block senescence. The simulations confirms that these pathways are able to trigger senescence independently. The simulation shows that pRb is essential to maintain the senescent state even when p16 and p53 are switched off, but the simultaneous inactivation of both p53 and pRB blocks senescence. In addition, the simulation shows that inactivation of the p16-pRb pathway is not essential to preserve the senescent state, however when p53-p21 pathway is inactivated, the senescent state is preserved.